Faktor-Faktor yang Mempengaruhi Orang Dewasa Mengikuti Pelatihan di LPK Sekai Japan - Rachmadika, Fasha; Matin, Ahmad Ghilman; Ramadhan, Deval Hananka; Laskono, Bayu Adi (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
Abstract. The need for job seekers rather than job creators has resulted in an abundance of graduates seeking employment. To address this issue, Education and Skills Institutions (LPK) have emerged as a solution, providing non-formal education where learners can acquire knowledge, attitudes, and skills. However, LPK educators have not fully grasped the adult learning approach. In February 2023, a research study was conducted at LPK Sekai Japan for three weeks with the goal of understanding the History and Theory of Adult Learning, assumptions of adult learning, and its application in learning. The research involved a three-stage process of Planning, Implementation, and Evaluation. The training aimed to equip participants with a comprehensive understanding of the History of Adult Learning Theory, assumptions of adult learning, and the skills necessary to apply these theories in learning at the LPK.